The effect of green bean juice and honey on increasing hb levels of adolescents who experience anemia - Ana Mariza; Kiswari Kiswari; Sunarsih Sunarsih; Wayan Aryawati (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Anemia remains a health concern among adolescents, with a national prevalence of 32% among girls aged 15–24 years. At Roudlatul Qur’an Islamic Boarding School in Metro City, 40% of female students were found to be anemic. Anemia causes fatigue, reduced concentration, poor academic performance, and future obstetric risks. Mung bean juice and honey contain iron, folic acid, and enzymes that support hemoglobin production naturally. Purpose: To determine the effect of mung bean juice and honey on increasing hemoglobin levels among anemic adolescents. Method: This study used a quantitative approach with a pre-experimental one-group pretest-posttest design. A total of 26 adolescent girls with mild anemia were selected through purposive sampling. Data were collected using observation sheets and analyzed using a paired sample t-test. Results: The average Hb level increased from 10.8 g/dL before intervention to 11.77 g/dL after. The statistical test showed a significant effect of mung bean juice and honey on increasing hemoglobin levels (p-value < 0.001). Conclusion: The administration of mung bean juice and honey effectively increases hemoglobin levels in adolescents with mild anemia. Suggestion: Adolescents are encouraged to regularly consume mung bean juice and honey. Islamic boarding schools should consider incorporating mung bean-based dishes into weekly meal plans.